Development of an Android Application Based on Quranic Exegesis Related to Fasting and Fidyah - Nur Afiyah binti Mahmud Fathi
The idea of this study is triggered for it is commonly known that when it comes to the development of the scientific and technology knowledge, it is being spearheaded by the Western where it continues to be dominated by Western scientists these days. Ironically, this scientific knowledge orientation is still not making progress anlong Muslim comnlunities due to lack of awareness to analyze and interpret the secrets of knowledge contained in the text of al-Qur'an especially when it comes to a scientific implementation in understanding the Qur'an itself. Fasting is the third pillar of Islam. Fasting during Ramadan is conlpulsory for every Muslim. Therefore, people who are unable to fast during Ramadan such as a woman in menstruation, or in childbirth bleeding, pregnant woman and nursing mother are allowed to break their fast. However, they need to replace fasting in other months. Most of the women have problems remembering how many days they missed their fasting in Ramadan and when they have to replace (qada ') fasting. The objectives of this research are: (1) To identify Quranic verses related to fasting and fidyah and to analyze Islanlic scholars' opinions of the related verses and analyze scholars' opinions of the related verses in the knowledge of Aqli which is in the scientific perspective; and (2) To develop an Android application for fasting and fidyah. This research will use qualitative by using text analysis as a method. To achieve the first objective of this research, the Quranic verses related to fasting and fidyah will be identified from siirah al-Baqarah which contained the related verses. While deductive method will be used to analyze the interpretation of Quranic exegesis from the Quranic verses that have been identified by using a thematic approach and also the relationship between the knowledge of Naqli and Aqli. To achieve the second objective, an Android application will be developed for the user to track fasting by using Mobile Application Development Lifecycle (MADLC) method. The significance of this research is to help those who wish to understand the words of Allah that are related to fasting and fidyah, in which lies the diversity of Muslims' understanding of al-Qur'an. By using this application, the users can track their fasting and know the amount of fidyah they need to pay based on the day and year they missed fasting as well as the information about fasting and fidyah based on Qur'an and Sunnah.